Hypothyroidism Induces a Moderate Steatohepatitis Accompanied by Liver Regeneration, Mast Cells Infiltration, and Changes in the Expression of the Farnesoid X Receptor - Rodríguez-Castelán, J.; Corona-Pérez, A.; Nicolás-Toledo, L.; Martínez-Gómez, M.; Castelán, F.; Cuevas-Romero, E. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Hypothyroidism is associated with the development of non-alcoholic steatohepatitis, but cellular mechanisms have been scarcely analyzed. Thyroid hormones regulate the synthesis and secretion of bile acids that are endogenous ligands of the farnesoid receptor (FXRα), which have been involved in the development of non-alcoholic steatohepatitis. However, the relationship between thyroid hormones and FXRα expression in the liver is yet unknown. Control (n=6) and methimazole-induced hypothyroid (n=6) female rabbits were used to evaluate the amount of lipids and glycogen, vascularization, hepatocytes proliferation, immune cells infiltration, and expression of FXRα. Student-t or Mann-Whitney U tests were carried out to determine significant differences. Hypothyroidism induced steatosis, glycogen loss, fibrosis, and a minor vascularization in the liver. In contrast, hypothyroidism increased the proliferation of hepatocytes and the infiltration of mast cells, but did not modify the number of immune cells into sinusoids. These changes were associated with a minor anti-FXRα immunoreactivity of periportal hepatocytes and pericentral immune cells. Our results suggest that hypothyroidism induces a moderate non-alcoholic steatohepatitis, alllowing the hepatic regeneration. The FXRα may be involved in the development of non-alcoholic steatohepatitis in hypothyroid subjects.
Keywords: thyroid hormones; liver; FXRα; NASH; methimazole